Implementasi Metode Adams Bashforth Moulton pada Persamaan Logistik Biner untuk Menganalisis Prediksi Tingkat Pertumbuhan Ekonomi - Nabilla, Sofia; Rakhmawati, Fibri (Jurnal Pendidikan Matematika : Judika Education, 2023)
ABSTRACT This research aims to determine the prediction of the economic growth rate of North Sumatra Province based on the implementation of Adams Bashforth Moulton in the binary logistics equation. The research method used is quantitative using the Adams Bashforth Moulton model with binary logistic equations. The research results show that the predicted level of economic growth in North Sumatra Province is in 2023 it will be 29,561,074.9 rupiah, in 2024 it will be 29,578,899 rupiah, in 2025 it will be 29,596,044.7 rupiah, in 2026 it will be 29,612,536.8 rupiah, in 2027 it will be 29,628,506.6 rupiah, in 2028 it will be 29,643,808.9 rupiah. Every year economic growth increases by an average of 16,877. The conclusion is that the implementation of the Adams Bashforth Moulton Method in the Binary Logistic Equation to Analyze Predictions of the Economic Growth Rate of North Sumatra Province can be categorized as valid in predicting.